2001
DOI: 10.1046/j.1440-1614.2001.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Validation of the Dysmorphic Concern Questionnaire

Abstract: Negative body beliefs are the hallmark of BDD. However, the existence of dysmorphic concern does not necessarily imply a diagnosis of BDD. The DCQ is a quick and efficient means of identifying dysmorphic concern in those who present with depression, OCD, social phobia or BDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 21 publications
(37 reference statements)
5
56
1
2
Order By: Relevance
“…Significant correlations were observed between the DCQ and impairment in different life domains; correlations were also observed between the DCQ and the Beck Depression Inventory (r = 0.49). In a second study with psychiatric inpatients, the DCQ showed high convergent validity with construct-related measures and discriminated between BDD patients and patients with other psychiatric disorders [Jorgensen et al, 2001]. In addition to the DCQ, the Center for Epidemiological Studies for Depression-Scale (CES-D) by Radloff [1977;German version by Hautzinger and Bailer, 1991] was used to assess general symptoms of depression.…”
Section: Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant correlations were observed between the DCQ and impairment in different life domains; correlations were also observed between the DCQ and the Beck Depression Inventory (r = 0.49). In a second study with psychiatric inpatients, the DCQ showed high convergent validity with construct-related measures and discriminated between BDD patients and patients with other psychiatric disorders [Jorgensen et al, 2001]. In addition to the DCQ, the Center for Epidemiological Studies for Depression-Scale (CES-D) by Radloff [1977;German version by Hautzinger and Bailer, 1991] was used to assess general symptoms of depression.…”
Section: Assessmentsmentioning
confidence: 99%
“…To prevent the psychological and economic costs of unnecessary and sometimes harmful treatment procedures, it is necessary to identify patients with BDD in dermatological samples when seeking treatment or surgery. The Dysmorphic Concern Questionnaire (DSQ) [Oosthuizen et al, 1998;Jorgensen et al, 2001], a short and economical self-rating instrument that screens for BDD symptoms, may prove beneficial in this identification process. The purpose of this study was to validate the DCQ as a screening instrument for BDD in dermatological outpatients.…”
Section: Introductionmentioning
confidence: 99%
“…The test is internally consistent with a reported alpha of 0.8. It has also been found [Jorgensen et al, 2001] that the DCQ discriminates well between those who do and do not meet criteria for BDD as assessed by the Body Dysmorphic Disorder Examination (BDDE) [Rosen et al, 1995] and between BDD patients, patients with disfiguring disorders and patients with non-disfiguring disorders [Stangier et al, 2003] The Multidimensional Perfectionism Scale (MPS). The MPS comprises three scales measuring self-oriented, other-oriented and socially prescribed perfectionism [Hewett and Flett, 1991].…”
Section: Instrumentsmentioning
confidence: 99%
“…The DCQ has been used in a number of cosmetic surgery studies (e.g., Castle et al, 2004;Kisely et al, 2002). The DCQ has demonstrated good psychometric properties, with a Cronbach's alpha of .80 (Jorgensen et al, 2001). Most of the variance (39%) is explained by a single factor and it shows strong correlations with measures of depression and social anxiety (Jorgensen et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The DCQ has demonstrated good psychometric properties, with a Cronbach's alpha of .80 (Jorgensen et al, 2001). Most of the variance (39%) is explained by a single factor and it shows strong correlations with measures of depression and social anxiety (Jorgensen et al, 2001). The internal consistency of the DCQ was high in both the pre-operative and post-operative survey of the current study (α = .85).…”
Section: Methodsmentioning
confidence: 99%